Cytotoxic and antibacterial activities of constituents from Calophyllum ferrugineum ridley - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher; Mohamed Zulkifli, Razauden (ACG Publications, 2016)
This study evaluated the chemical composition of Calophyllum ferrugineum, cytotoxicity against human breast cancer (MCF-7) and human lung carcinoma (A-549) cell lines as well as antibacterial activities against two Gram-positive bacteria, S. aureus and B. subtilis and two Gram-negative bacteria, P. aeruginosa and E. coli. Phytochemical investigations of the bark extract yielded isoapetalic acid (1), apetalic acid (2), 6-hydroxy-2-methoxyxanthone (3) and ent-epicatechin (4). Meanwhile, betulinic acid (5), protocatechuic acid (6) and amentoflavone (7) were isolated from the leave extract. Isoapetalic acid (1) and apetalic acid (2) exhibited cytotoxic activities towards both cancer cell lines and both Gram-positive bacteria. Compounds (3-7) were inactive or showed moderate activities towards cytotoxic and antibacterial tests. This study presents the first report on the phytochemicals investigation from C. ferrugineum and all compounds are reported for the first time from this source.